Hadith Discourse Networks in Al-Munir Magazine (1911–1915): A Social Network Analysis of the Representation and Contestation of Prophetic Traditions - Nandi Pinto; Domi Sepri (Al-Qudwah, 2026)
This study aims to uncover the structure of the hadith network in Al-Munir magazine, with a particular focus on three main aspects: the distribution of hadith, the centralization of textual sources, and the works that function as authoritative references. This research employs a Social Network Analysis (SNA) approach by mapping 25 hadith citations from 54 issues of the magazine. The data were analyzed using degree centrality, betweenness centrality, eigenvector centrality, and 2-mode cohesion, utilizing UCINET 6.813, based on references to the Kutub al-Tis’ah. The findings indicate that 19 citations present hadith in their original Arabic form, while 1 hadith is a translation provided by the magazine’s authors; meanwhile, 35 sections do not cite any hadith at all. In terms of hadith authenticity, 54% are classified as ṣaḥīḥ with uninterrupted chains of transmission (sanad), 1% as ḥasan ṣaḥīḥ, and the remaining 45% as ḍaʿīf, primarily due to deficiencies in their chains of transmission. Sunan Abū Dāwūd emerges as the primary broker (betweenness = 20.000), functioning as a bridge among canonical texts. Musnad Aḥmad ibn Ḥanbal appears as the most prominent source, with the highest out-degree (7.000) and eigenvector centrality (0.441), indicating its role as an open and inclusive repository. Ṣaḥīḥ Muslim is more active in disseminating references compared to Ṣaḥīḥ al-Bukhārī, highlighting a distinction between active and passive forms of authority. The high level of transitivity (0.669) reveals a collective mechanism of legitimacy based on cross-textual confirmation. Based on these findings, the study concludes that the Kaum Mudo did not reject tradition; rather, they reconstructed religious authority based on principles of interconnectivity, contextual relevance, and social function. Print media functioned as a tool for redistributing authority, shifting the study of hadith from a hierarchical discipline toward a more open and responsive system of knowledge.